Evaluation Study Of Sign And Mark Placement On Road Geometrics In Lhokseumawe City (Case Study Of Merdeka Road, Lhoseumawe City) - Erlita Erlita; David Sarana; Lis Ayu Widari; Yovi Chandra; Nura Usrina; Julsena Julsena; Ulfa Zahra Gultom (LPPM Universitas Malikussaleh, 2024)
The road section Merdeka is a city road section that is a secondary road in the city, with a fairly good road surface condition with asphalt paving and most of this road still has many trees on the right and left sides of the road. The purpose of this study was to determine the amount of road equipment needed as a monitoring tool for the implementation of traffic management and engineering in the context of road safety. The analysis method used is qualitative and constitutive descriptive analysis. The type of research conducted is a combination of surveys and direct field observations as well as literature (library) related to the placement of signs and markings in accordance with urban road traffic standards. This study was conducted on the road section Merdeka with the consideration that the road section has a fairly high traffic density. Traffic signs are needed on this road segment as many as 158 units consisting of 34 command signs, 49 guide signs, 32 warning signs, and 43 prohibition signs.